ANALISIS HUBUNGAN KUANTITATIF STRUKTUR DAN AKTIVITAS ANTINOSISEPTIF SENYAWA FLAVONOID PADA DAUN Muntingia Calabura L. MENGGUNAKAN METODE PERHITUNGAN HARTREE FOCK - Azrina Nindia; Rahmat Gunawan (PROSIDING SEMINAR KIMIA, 2017)
Quantitative relationship analysis of the antinosiseptive structure of flavonoid compound on Muntingia Calabura L. leaf has been done. This research used Hartree Fock and Correlation Analysis method using QSAR. The inhibition activity of flavonoid compound and dipole moment are independent variable, while the dependent variable is the active center of the flavonoid compound. The results obtained from structural relations and antinociceptive activity are very strong with a correlation value of 1,00. Then, the result can be significantly influenced on C3 atom and dipole moment of drug with QSAR formula that is A = 2,15 + 0,03 C3 – 0,17 D. Keywords : Flavonoid, Antinociceptive, Hartree Fock, QSAR